MORPHOLOGICALAND MORPHOMETRIC STUDIES ON PROTOSCOLECES ROSTELLAR HOOKS OF ECHINOCOCCUS GRANULOSUS FROM PERU VISUALIZED BY SEVERAL MICROSCOPIC TECHNIQUES - Almeida B, Fernanda (2009)
This study was undertaken to expand the current knowledge of the morphology and morphometry of rostellar hooks of protoscoleces from the metacestode E. granulosus. Protoscoleces were isolated from livers and lungs of naturally infected ovines and bovines obtained from abattoirs in Peruvian provinces (Arequipa, Cuzco, Puno, Huancavelica and Junin). Brightfield microscopy, confocal laser scanning microscopy, differential interference contrast and variable pressure scanning electron microscopy were used. Morphometry was made using computer image analysis. The application of these assay indicated that the large hooks frequently had thin guards and an irregular surface between the guard and handle. Data also showed that the small hooks presented rounded and stout guards. The blade did not show any relevant feature. No clear morphological distinction was observed between large and small hooks. Phenotypical polymorphism was evident in the shape and size of hooks. In conclusion, the current data show that large and small rostellar hooks have morphological polymorphism. Because the application of this knowledge for taxonomic study is limited, for this end morphometry techniques are required. Our study demonstrated the usefulness of combining conventional and new morphological tools to help to solve unresolved matters with regards to rostellar hooks features.